Increasing productivity of an intensive rice based system through site specific nutrient management in Western Terai of Nepal - Marahatta, Santosh (Journal of Agriculture and Environment, 2018)
Improving nutrient management through site specific nutrient management (SSNM) can increase grain yield and maintain appropriate yield attributes per unit of fertilizer applied through harmonized uptake, utilization and metabolism of major nutrients. On-farm experiments were conducted from 2011-2013 at Sunawal, Nawalparasi. SSNM dose was calculated by accounting for indigenous nutrient supply, yield goal, nutrient demand and fertilizer efficiency. SSNM decreased nitrogen and phosphorus application by 4 and 28% while demanded 80% more potassium and increased grain yield by 6% over recommended practice. As compared to the farmers fertility management practice (FFP), SSNM increased grain yield by 35%. Reducing 25% of SSNM dose was equally effective as recommended practice of nutrient application. Only improving the potassium application (+32 kg ha-1) on FFP, yield was increased by 17%. Leaf color charts (LCC) improve nitrogen management and proved as crucial component of SSNM as 0.3 t ha-1 more yield over three split nitrogen applications of SSNM dose.